THE IMAGE OF A WOMAN IN FOLKLORE AS A FOLK TRADITION - Aslanova Gulara Chingiz (International Journal of Innovative Technologies in Social Science, 2024)
This study explores the multifaceted portrayal of women in folklore, focusing on their roles as creators, transmitters, and subjects of oral traditions. Employing a feminist folklore approach, the research aims to elucidate the complex dynamics of gender, power, and representation within folkloric narratives. The methodology combines extensive literature review, comparative analysis of folkloric texts across various Turkic cultures, and critical interpretation informed by feminist theory. The findings reveal that while women’s folklore often reflects the dominant patriarchal values, it also serves as a medium for expressing female solidarity, subverting gender norms, and asserting women’s agency. The study highlights the significance of women’s oral traditions as a vital source for understanding their lived experiences, cultural contributions, and strategies of resistance in maledominated societies. The research contributes to the growing body of feminist folklore scholarship and underscores the importance of integrating women’s perspectives into the mainstream folklore discourse. Further research is needed to explore the regional variations, historical transformations, and contemporary adaptations of women’s folkloric practices.